Modern conducted labor is medically assisted - Prvulović Mirjana B.; Rodić Danijela O. (Srpsko lekarsko drustvo, 2017)
Introduction: First child delivery stage lasts 12-16 hours not including any medications, while the second child delivery stage and grand multiparity last a couple of hours shorter. Oxytocin (Syntocinon®) is drug that facilitates well-fed delivery, therefore, induced labor assisted by peridural lasts approximately 4 hours less than natural labor not supported by any medication. Aim: To make quantitative analysis of the medically assisted childbirth and spontaneous vertex delivery within three years (2014-2016). Methodology: This paper is part of a non-commercial, retrospective, IV phase epidemiological study. The study was conducted at the Clinical Centre 'Dr Dragiša Mišović, Dedinje', Hospital for Gynecology and Obstetrics. The data are obtained from the ZIS Monthly-Yearly Heliant Reports of the Hospital for Gynecology and Obstetrics, Delivery room. Results: In the Clinical Centre 'Dr Dragiša Mišović, Dedinje', Hospital for Gynecology and Obstetrics, Delivery room there is over 2000 childbirths annually. Number of pharmacologically assisted labors was 1290 or (62%) in 2014, in 2015 was 1318 or (61%) and in 2016 was 1286 or (60%).Using syntocinon, there was 585 or (28%) in 2014, in 2015, 513 or (28%) and in 2016, 639 or (30%) cesarean sections, urgent, planned and elective labors. Of the total 80% of newborns received Apgar score 9 (nine). Conclusions: Labor induced by medication is a joint choice of a midwifes and doctors health team because the flow of labor can be anticipated and influenced at any moment.